2015
DOI: 10.1128/iai.02234-14
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Veillonella parvula to Pseudomonas aeruginosa-Mediated Pathogenicity in a Murine Tumor Model System

Abstract: fThe recent finding that high numbers of strict anaerobes are present in the respiratory tract of cystic fibrosis (CF) patients has drawn attention to the pathogenic contribution of the CF microbiome to airway disease. In this study, we investigated the specific interactions of the most dominant bacterial CF pathogen, Pseudomonas aeruginosa, with the anaerobic bacterium Veillonella parvula, which has been recovered at comparable cell numbers from the respiratory tract of CF patients. In addition to growth comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 58 publications
1
33
0
2
Order By: Relevance
“…The model is also applicable for unraveling the complex interactions that occur during P. aeruginosa coinfections with other bacteriatypically with Staphylococcus aureus or anaerobes (38). Furthermore, it is possible to evaluate the efficacy of classical antimicrobial agents against P. aeruginosa biofilm infections and optimize the combinations and application regimens thereof.…”
Section: Discussionmentioning
confidence: 99%
“…The model is also applicable for unraveling the complex interactions that occur during P. aeruginosa coinfections with other bacteriatypically with Staphylococcus aureus or anaerobes (38). Furthermore, it is possible to evaluate the efficacy of classical antimicrobial agents against P. aeruginosa biofilm infections and optimize the combinations and application regimens thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accord with recently reported associations between these taxa and cancer. Guerrero-Preston et al (2016) demonstrated that Streptococcus Haemophilus and Veillonella were the most abundant taxa in the saliva of OSCC patients, and Pustelny et al (2015) showed that Veillonella parvula preferentially colonizes neoplastic tissues. Higher proportions of Haemophilus and Neisseria have been detected in patients with oral leukoplakia (Hu et al 2016) and oral erosive lichen planus (Wang et al 2016), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this, Prevotella intermedia was shown to induce a humoral immune response in PWCF and to mediate an influx of neutrophils and macrophages, thereby increasing CF airway inflammation (12). Furthermore, anaerobes belonging to the oropharyngeal flora have been shown to enhance the virulence of P. aeruginosa in a number of infection models (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%